The Global and Regional Challenge of Pan-Antibiotic Resistance: A Review of Emerging Threats and Mechanisms - Sharique Ahmad; Dilshad Ali Rizvi; Md Shumayel Athar Khan; Subuhi Anwar; Ruvy Verma; Mayuri Agarwal (International Journal of Antibiotics, 2026)
Antimicrobial resistance (AMR) is one of the major and most intricate threats to the health of the 21st century as it is core to the undermined expertise of the common clinical practice and public health security worldwide. The problem is characterized by the extensive development of bacterial pathogens into extremely drug-resistant (XDR) and pan-drug-resistant (PDR) so- called superbugs faster than it can be done with therapeutics. It is a synthesis of molecular processes that drive this resistance and the critical issues are critically looked at on the global level and a focal lens on the unique and increased burden in India. We explore the effectiveness and shortcomings of the existing interventions such as antimicrobial stewardship and alternative therapies to contextualize a needed direction into the future of continuing the use of the existing antibiotics and encouraging new one development.
Keywords: Therapies; antibiotics; antimicrobial resistance; multidrug-resistant; pathogens